2022
DOI: 10.1111/gwat.13164
|View full text |Cite
|
Sign up to set email alerts
|

Mapped Predictions of Manganese and Arsenic in an Alluvial Aquifer Using Boosted Regression Trees

Abstract: Manganese (Mn) concentrations and the probability of arsenic (As) exceeding the drinking-water standard of 10 μg/L were predicted in the Mississippi River Valley alluvial aquifer (MRVA) using boosted regression trees (BRT). BRT, a type of ensemble-tree machine-learning model, were created using predictor variables that affect Mn and As distribution in groundwater. These variables included iron (Fe) concentrations and specific conductance predicted from previously developed BRT models, groundwater flux and age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
(134 reference statements)
1
4
0
Order By: Relevance
“…Conversely, discharge areas are more likely to be suboxic and the model correctly predicts that suboxic conditions are likely in the Mississippi Embayment , and in the trough of the Central Valley of California . Similarly, the high probability of Mn concentrations ≥50 μg/L in the Mississippi Embayment (Figure ) is consistent with previous work …”
Section: Results and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Conversely, discharge areas are more likely to be suboxic and the model correctly predicts that suboxic conditions are likely in the Mississippi Embayment , and in the trough of the Central Valley of California . Similarly, the high probability of Mn concentrations ≥50 μg/L in the Mississippi Embayment (Figure ) is consistent with previous work …”
Section: Results and Discussionsupporting
confidence: 88%
“… 110 Similarly, the high probability of Mn concentrations ≥50 μg/L in the Mississippi Embayment ( Figure 7 ) is consistent with previous work. 111 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning (ML) methods are becoming more widely utilized in the field of environmental science and can identify patterns in data not easily accomplished with traditional statistical methods . Several different ML approaches have been applied to predicting groundwater quality at regional and national scales including random forest and boosted regression trees. Recently, extreme gradient boosting (XGB) models have been developed to predict manganese concentrations in the North Atlantic Coastal Plain aquifer system and nitrate concentrations in groundwater across the CONUS . The nitrate study found that the XGB model outperformed a boosted regression tree model based on the root-mean-square error from the cross-validation folds during model tuning.…”
Section: Introductionmentioning
confidence: 99%
“…Constituent concentrations in upper-crustal materials are commonly sufficient that dissolution of small fractions during water–rock interaction can cause an exceedance of concentration thresholds for intended water use (Table S1 ). Concentrations of many geogenic constituents increase with groundwater age and flowpath length but also vary with aquifer lithology and hydrogeochemical conditions including pH and redox (DeSimone & Ransom, 2021 ; Erickson et al 2021a , 2021b ; Knierim et al, 2022 ; Lindsey et al, 2021 ; Stackelberg et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%